(3x+5y)-(4x+11)=0

Simple and best practice solution for (3x+5y)-(4x+11)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+5y)-(4x+11)=0 equation:


Simplifying
(3x + 5y) + -1(4x + 11) = 0

Remove parenthesis around (3x + 5y)
3x + 5y + -1(4x + 11) = 0

Reorder the terms:
3x + 5y + -1(11 + 4x) = 0
3x + 5y + (11 * -1 + 4x * -1) = 0
3x + 5y + (-11 + -4x) = 0

Reorder the terms:
-11 + 3x + -4x + 5y = 0

Combine like terms: 3x + -4x = -1x
-11 + -1x + 5y = 0

Solving
-11 + -1x + 5y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + -1x + 11 + 5y = 0 + 11

Reorder the terms:
-11 + 11 + -1x + 5y = 0 + 11

Combine like terms: -11 + 11 = 0
0 + -1x + 5y = 0 + 11
-1x + 5y = 0 + 11

Combine like terms: 0 + 11 = 11
-1x + 5y = 11

Add '-5y' to each side of the equation.
-1x + 5y + -5y = 11 + -5y

Combine like terms: 5y + -5y = 0
-1x + 0 = 11 + -5y
-1x = 11 + -5y

Divide each side by '-1'.
x = -11 + 5y

Simplifying
x = -11 + 5y

See similar equations:

| 17y-5x=46 | | .14(14+3.5)-3q=9 | | -5=r-13 | | 2y+3=3(-2)-7 | | x-1(4x-7)=5x-(x+21) | | 3(x-9)=-39-x | | 7x+3=-7.5 | | (-A-5B+2)5AB= | | -4+6x=-34 | | 0.3(r+2)=-1.0(-2r-4) | | 6t^2+2t=2t(3t+1) | | 2y+3=3(0)-7 | | -7(p-8)= | | -2v-14=8(v+2) | | 4t=38+2t | | n-8=22+4 | | 3(4+4n)=18n+12-6n | | -5(x+7)= | | (2x+4)x=240 | | 6/15=3/x | | 2n^2=90 | | x(6)=60 | | n+3=17+4 | | 9h+11=5h-17 | | 2x(2x)= | | x(13)=52 | | 8x+9y=818 | | 400-313=x | | 6(b+4)=0 | | -9(6+u)=2u-10 | | 132=12(n+9) | | -8x+4(1+5x)=-6-14 |

Equations solver categories